Examining Computer Use by Hospitalized Children and Youth. Issue 4 (2nd October 2017) - Nicholas, David B.; Chahauver, Anu
ABSTRACT: Hospitalized children and their families face information and support needs that may be augmented by Internet access. Using a qualitative description methodology, this study examined computer/technology use by hospitalized children. Thirteen pediatric patients who accessed hospital-based computers while hospitalized and 11 parents participated in qualitative interviews. Children used computers for gaming, chatting with peers, homework, social media, and general browsing. Benefits of computer use included distraction from unpleasant treatments, social support, and normalization of experience. Barriers to use included computer inaccessibility, lack of privacy, and technology-based challenges. Computer access appears to offer a constructive role in ameliorating pediatric hospitalization experiences.